Konsep Pendidikan Islam Moderat dalam Perspektif Kitab Ta'limul Muta'allim: Pendekatan dan Relevansinya dalam Konteks Pendidikan Masa Kini - Miswanto, Miswanto; Muhammad Farih; Imam Nur Aziz (Rayah Al-Islam, 2024)
Moderate Islamic education, which emphasises the values of balance, tolerance and openness, plays an important role in creating a harmonious and peaceful society. Syaikh Az-Zarnuji's Ta'limul Muta'allim provides valuable guidance on Islamic education that integrates religious teaching with noble character building. This article aims to explore the concept of moderate Islamic education in the perspective of Ta'limul Muta'allim and its relevance in facing current educational challenges. Through the literature research method, this article identifies the concept of moderate Islamic education taught in the book, which includes how the curriculum of moderate Islamic education, the objectives of moderate Islamic education, the role of a teacher in moderate Islamic education, students in moderate Islamic education and methods of moderate Islamic education and its relevance to education today. The results show that moderate Islamic education described in Ta'limul Muta'allim has five educational concepts and is relevant to today's education and can even form a generation that is not only intelligent in the field of religion, but also able to adapt to the times and maintain social diversity. Thus, this educational concept can be a solution in strengthening moderate religious understanding and avoiding potential social conflicts caused by differences in understanding.